Fotokarcinogeneza - Kansky, Aleksej (Radiology and oncology (Ljubljana), 1999)
Photocarcinogenesis is a complex and still not fully explored process. Epidemiological studies as well as animal experiments show that wave lenghts in the range of 320-280 nm (UV B) are the main pathogenetic factor. Skin complexion and other genetic factors are however also important. The UV B raysare injuring directly the molecules of deoxyribonucleic acidic in the nuclei keratinocytes, fibroblast and Langerhans; cells, but the inducement of various molecules (chromatophores) into an excited stage is a further pathogenetic mechanism. This situation lasts only fraction of a ssecond and the relase of various forms of energy, which follows, is injuring cells and their organel as well as producing noxious products, e.g., pereoxides. In the inducement of carcinogenesis further mechanisms are usually coivolved as an impaired action of repartion enzmes, immunosuppression of T lymphocytes by UV B, expression of oncogenes and antiocogenes and others. A short review of th eabove mentioned processes is given.
Keywords: Adverse effects; etiologija; Etiology; karcinogeneza; kožne spremembe; novotvorbe; onkologija; Skin neoplasms; škodljivost; ultravijolično sevanje; Ultraviolet rays